2023
DOI: 10.3390/v15061387
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Highly Pathogenic Avian Influenza A (H5) in Poultry in Nigeria, 2021–2022

Abstract: In 2021, amidst the COVID-19 pandemic and global food insecurity, the Nigerian poultry sector was exposed to the highly pathogenic avian influenza (HPAI) virus and its economic challenges. Between 2021 and 2022, HPAI caused 467 outbreaks reported in 31 of the 37 administrative regions in Nigeria. In this study, we characterized the genomes of 97 influenza A viruses of the subtypes H5N1, H5N2, and H5N8, which were identified in different agro-ecological zones and farms during the 2021–2022 epidemic. The phyloge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…In a recent report on the diversity and evolution of highly pathogenic avian influenza in Nigeria, 36 2023 confirm the detection of H5N1, H5N2, and H5N8 of the clade 2.3.4.4b in commercial poultry farms across different states in Nigeria. Comparison of the H5Nx viruses of the clade 2.3.4.4b viruses detected and characterized in poultry in this study 36 revealed that these poultry viruses are genetically distinct from the ones identified in Hadejia Nguru wetland. The adduced reasons for this genetic divergence can include the inadequate/limited surveillance activities for HPAI in wild birds in wetlands across the country.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…In a recent report on the diversity and evolution of highly pathogenic avian influenza in Nigeria, 36 2023 confirm the detection of H5N1, H5N2, and H5N8 of the clade 2.3.4.4b in commercial poultry farms across different states in Nigeria. Comparison of the H5Nx viruses of the clade 2.3.4.4b viruses detected and characterized in poultry in this study 36 revealed that these poultry viruses are genetically distinct from the ones identified in Hadejia Nguru wetland. The adduced reasons for this genetic divergence can include the inadequate/limited surveillance activities for HPAI in wild birds in wetlands across the country.…”
Section: Discussionmentioning
confidence: 82%
“…This implies that as these birds migrate from one continent to another, they can transmit the virus to the resident aquatic birds, which can then further disseminate the virus across the region. In a recent report on the diversity and evolution of highly pathogenic avian influenza in Nigeria, 36 2023 confirm the detection of H5N1, H5N2, and H5N8 of the clade 2.3.4.4b in commercial poultry farms across different states in Nigeria. Comparison of the H5Nx viruses of the clade 2.3.4.4b viruses detected and characterized in poultry in this study 36 revealed that these poultry viruses are genetically distinct from the ones identified in Hadejia Nguru wetland.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations